2023
DOI: 10.1002/cnma.202200494
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Pt Single Atom and Clusters toward Selective Glycerol Oxidation

Abstract: Selective oxidation of excess glycerol to glyceric acid is a significant reaction but the reaction is inhibited by the CÀ H activation that has a high energy barrier. Here, we introduced Pt single atom species (PtÀ OÀ Ce) into Pt/CeO 2 , which gave a high glycerol conversion of 90.9% with a high glyceric acid selectivity of 83.2% under the mild reaction conditions (T = 100 °C, O 2 flow of 5 mL min À 1 , and non-alkaline). The CÀ H bond can be easily adsorbed and activated over PtÀ OÀ Ce, which facilitated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, activation of the C–H on the terminal −CH 2 OH of glycerol has a higher energy barrier in its selective oxidation to glyceric acid. Luo et al fabricated a (Pt 1 –Pt n )/CeO 2 catalyst by an impregnation method, which showed significantly higher activity than those of the respective Pt 1 /CeO 2 and Pt/CeO 2 NCs in glycerol oxidation, offering a 183.7 h –1 TOF value . The synergism between Pt SAs and Pt clusters efficiently promoted the reaction, where Pt clusters adsorbed the primary C–O/CO bonds and the adjacent Pt SAs activated the C–H bonds, thus reducing the activation barrier of glycerol oxidation.…”
Section: Application Of Sacs In Biomass Chemical Conversionmentioning
confidence: 99%
“…However, activation of the C–H on the terminal −CH 2 OH of glycerol has a higher energy barrier in its selective oxidation to glyceric acid. Luo et al fabricated a (Pt 1 –Pt n )/CeO 2 catalyst by an impregnation method, which showed significantly higher activity than those of the respective Pt 1 /CeO 2 and Pt/CeO 2 NCs in glycerol oxidation, offering a 183.7 h –1 TOF value . The synergism between Pt SAs and Pt clusters efficiently promoted the reaction, where Pt clusters adsorbed the primary C–O/CO bonds and the adjacent Pt SAs activated the C–H bonds, thus reducing the activation barrier of glycerol oxidation.…”
Section: Application Of Sacs In Biomass Chemical Conversionmentioning
confidence: 99%
“…Finally, synergy in tandem requiring high proximity between SAs and NPs was also observed for glycerol selective hydrogenation to glyceric acid on Pt SA + NP /CeO 2 [93] and Pt SA + NP / CuÀ CuZrO x [16c] catalysts. In that case, some steps of the mechanism were proposed.…”
Section: Synergy In Tandem or Binary Complementary Effectmentioning
confidence: 99%